1997
DOI: 10.1159/000244422
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Bilirubin on the Antioxidant Capacity of Plasma in Newborn Infants

Abstract: In vitro, bilirubin is a strong antioxidant, but in vivo its capacity to act as a scavenger of toxic oxygen radicals remains poorly documented. The aim of this study was to evaluate if bilirubin had antioxidant properties in jaundiced infants. The antioxidant capacity of neonatal plasma was measured in Trolox equivalents (TEAC, mmol/l) and correlated in vitro with plasma bilirubin concentrations (r2 = 0.99). Plasma TEAC was compared before and after exchange transfusions for neonatal hyperbilirubine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
0
4

Year Published

1999
1999
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(94 citation statements)
references
References 17 publications
(25 reference statements)
2
87
0
4
Order By: Relevance
“…Analysis of the contribution of bilirubin to antioxidant status in neonates has shown that there is a strong correlation between bilirubin levels and total plasma antioxidant activity (Gopinathan et al, 1994). Similarly, other studies in neonates have shown that bilirubin levels that are raised to below toxic levels do not pose any health risk, and may exert a positive effect on total antioxidant power (Belanger et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Analysis of the contribution of bilirubin to antioxidant status in neonates has shown that there is a strong correlation between bilirubin levels and total plasma antioxidant activity (Gopinathan et al, 1994). Similarly, other studies in neonates have shown that bilirubin levels that are raised to below toxic levels do not pose any health risk, and may exert a positive effect on total antioxidant power (Belanger et al, 1997).…”
Section: Discussionmentioning
confidence: 96%
“…Conversely, at low concentrations (<1μM), bilirubin has potent anti-oxidant properties, as has been demonstrated in cells, animal models, and in clinical studies [25,47,140,144,[146][147][148]. The mechanism of its antioxidant effects involves effective scavenging of oxidant free radicals by bilirubin/biliverdin redox cycling.…”
Section: A Anti-oxidant and Anti-apoptotic Properties Of Bilirubinmentioning
confidence: 99%
“…Bilirubin accounts for the bulk of plasma antioxidant activity (74,75,80). Preterm infants with elevated plasma bilirubin levels suffer from less oxidative-stress injuries (81).…”
Section: Pathophysiologymentioning
confidence: 99%